SELECTION OF TEMPORARY REHABILITATION LOCATION AFTER DISASTER: A REVIEW - Anand, Abhigyan; Jethoo, A S; Sharma, Gunwant (European Scientific Journal, ESJ, 2015)
Temporary rehabilitation is extremely important to recover after disaster allowing people to return back to their normal activities like work, school, cooking, housekeeping etc. This study recapitulates the different models used for the selection of temporary rehabilitation location after different disaster. It explains various guiding principles, selection criteria, minimum standard for victims to be provided, various tools and techniques used for locating the effective site. Basic services like health facility, transportation, accessibility and livelihood are primary concern while selecting any site for temporary resettlement.